The impact of premarital cycling on early marriage - Vennum, Amber V.; Johnson, Matthew D. (My University, 2014)
Using a sample of 564 newlywed couples and the enduring dynamics model of marriage (Caughlin, Huston, & Houts, 2000), we examined the impact of premarital cycling (breaking up and renewing) on the entrance into marriage and relationship dynamics over the first five years. Consistent with the enduring dynamics model, results demonstrated cyclical couples (compared to non-cyclical couples) exhibited worse adjustment on a variety of relationship indicators at the entrance to marriage and were more likely to experience a trial separation over the first five years. Dyadic parallel process growth curve analysis further revealed that premarital cycling predicted lower initial relationship satisfaction that was sustained over the first five years of marriage. Implications for theory, research, and intervention with premarital couples are discussed. These results provide evidence that courtships characterized by breakups and renewals represent a relational vulnerability with negative implications extending years into the future.
Keywords: Courtship; Enduring dynamics model; Newlywed marriage; Preventing marital distress; Relationship cycling; Marital satisfaction